Reproductive Biology and Feeding Ecology of The Blue Swimming Crab (Portunus pelagicus) in Northern Coastal Waters, Sri Lanka - S S K Haputhantri,; K H K Bandaranayake,; M I G Rathnasuriya,; K G S Nirbadha,; S J W W M M P Weerasekera,; A A S H Athukoorala,; R A M Jayathilaka,; H A C C Perera,; S Creech, (Tropical Life Sciences Research, 2022)
Blue swimming crab (Portunus pelagicus) fishery has emerged to become an important export-oriented fishery in Sri Lanka over a decade and recently resulted in a rapid increase in the exploitation. The present study attempts to understand the reproductive biology and feeding ecology of blue swimming crab which will be vital in the management of capture fishery. Five major landing sites in the Jaffna district in Northern Sri Lanka, where blue swimming crab is frequently landed throughout the year were selected for the study. Biological parameters relating to sex, carapace width, body weight, maturity, and egg sac colour with egg sac weight were recorded at the field from November 2014 to October 2015. Randomly selected crab samples were brought to the laboratory and analysed for their maturity stages, length at first maturity, Gonadosomatic Index, fecundity, and gut contents. The study revealed that male crabs mature at a smaller size than females. The sex ratio varied greatly with time and males were always dominant in the catch. The blue swimming crabs in the Northern waters of Sri Lanka spawn throughout the year, with two spawning peaks in February and May. The total fecundity of ovigerous blue swimming crab increased with increased carapace width and body weight and it ranged from 123,482 to 3,179,928 eggs, with an average of 884,982 ± 676,420. A remarkably higher percentage of empty stomachs were observed under the present study in both mature and immature crabs and this could be due to lack of food availability in the environment and different digestibility rates of food items. The diet of blue swimming crab is highly variable reflecting the ability to adopt to different modes of feeding.